Equality and Justice as Keys to Building A Synodal Church - John Karuvelil (Asian Horizons, 2025)
Synodality, ‘walking together’ is at the heart of Christian vocation and mission. Synodality can happen only in communion. For us Christians, our communion is modelled on the Trinitarian God—the Father, the Son and the Spirit, who lives communion and synodality in its perfect form. Equality and justice are keys to synodality. In the absence of any of these two the question of synodality becomes moot. I have tried to explain this in this article, first, by explaining the foundations of equality for us Christians which are basically two—equality at the level of creation, created in the image and likeness of God and bearing equal dignity as children of God, and equality that is received by the fact of our baptism into Christ and, therefore, equality as Christians and as disciples of Christ; and second, by looking into the various dimensions justice, like common good, subsidiarity, solidarity, communion, participation, option for the poor, etc. and explaining the importance of each of these aspects for synodality and the building up of a synodal Church.